Digital education during pandemic and situation in Kazakhstan: current state and forecasts (Eurasian Journal of Philology Science and Education, 2023)
The Internet has changed all areas of human activity and education is no exception. A new term “digital education” has appeared with the development of Internet technologies in education. This article describes the main benefits of digital education associated with the Covid-19 pandemic, when people were forced to adjust their lives to the current situation in the shortest possible time.The Covid-19 pandemic has disrupted the functioning of higher education around the world, including in Kazakhstan. The forced transformation of the educational process has become a big test for Kazakhstani universities both in terms of changing the entire format of education, and in terms of material support. At the same time, the activities of universities received a powerful incentive to reform the entire education system, when the digitalization of the educational process came to the fore. The article provides an overview of the platforms that have been developed during the described period (Zoom, Microsoft Teams, Google Classroom, Kundelik, etc.). Particular attention is paid to the analysis of the “univer.kaznu.kz” platform, which is a large-scale platform successfully tested by teachers, students and employees of al-Farabi KazNU before 2020 and developed during the quarantine period.Key words: virtual classrooms, online etiquette, digital transformation of education, distance learning, pandemic, quarantine, school online format, university online format